1998
DOI: 10.1038/sj.onc.1201506
|View full text |Cite
|
Sign up to set email alerts
|

Brca1 and Brca2 expression patterns in mitotic and meiotic cells of mice

Abstract: The mouse homologues of the breast cancer susceptibility genes, Brca1 and Brca2, are expressed in a cell cycle-dependent fashion in vitro and appear to be regulated by similar or overlapping pathways. Therefore, we compared the non isotopic in situ hybridization expression patterns of Brca1 and Brca2 mRNA in vivo in mitotic and meiotic cells during mouse embryogenesis, mammary gland development, and in adult tissues including testes, ovaries, and hormonally altered ovaries. Brca1 and Brca2 are expressed concor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

9
57
0
1

Year Published

1998
1998
2008
2008

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 83 publications
(67 citation statements)
references
References 19 publications
9
57
0
1
Order By: Relevance
“…As illustrated in Figure 2a, Bard1 transcripts of approximately 6.0 and 3.0 kilobases are especially prevalent in RNA from spleen and testes (lanes 3 and 8, respectively), but not from heart, brain, lung, liver, skeletal muscle or kidney. The same expression pattern was obtained upon hybridization with pE18, a cDNA probe containing codons 8 ± 301 of mouse Brca1 (Bennett et al, 1995); in accord with previous reports (Abel et al, 1995;Bennett et al, 1995;Lane et al, 1995;Zabludo et al, 1996;Blackshear et al, 1998), this probe detects a major polyadenylated RNA species of 7.5 kilobases in the spleen and testes of adult mice (Figure 2b). The abundance of Bard1 and Brca1 transcripts in spleen and testes is especially striking given that these samples displayed the lowest levels of hybridization with the GAPDH control (Figure 2c; lanes 3 and 8).…”
supporting
confidence: 90%
“…As illustrated in Figure 2a, Bard1 transcripts of approximately 6.0 and 3.0 kilobases are especially prevalent in RNA from spleen and testes (lanes 3 and 8, respectively), but not from heart, brain, lung, liver, skeletal muscle or kidney. The same expression pattern was obtained upon hybridization with pE18, a cDNA probe containing codons 8 ± 301 of mouse Brca1 (Bennett et al, 1995); in accord with previous reports (Abel et al, 1995;Bennett et al, 1995;Lane et al, 1995;Zabludo et al, 1996;Blackshear et al, 1998), this probe detects a major polyadenylated RNA species of 7.5 kilobases in the spleen and testes of adult mice (Figure 2b). The abundance of Bard1 and Brca1 transcripts in spleen and testes is especially striking given that these samples displayed the lowest levels of hybridization with the GAPDH control (Figure 2c; lanes 3 and 8).…”
supporting
confidence: 90%
“…The expression pattern of BRCA1 throughout development also suggests its importance in tissues that undergo rapid proliferation and terminal di erentiation (Lane et al, 1995;Marquis et al, 1995;Blackshear et al, 1998;Magdinier et al, 1999). Removal of the transcriptional block at the position of intron 1 which we have identi®ed in this study would be an e ective way to increase BRCA1 levels in a timely manner for subsequent molecular events.…”
Section: Discussionmentioning
confidence: 94%
“…The progressive changes in Brca1 expression during mouse embryogenesis (8) also imply a role for Brca1 in the differentiation process. In addition, variations of Brca1 expression are observed during postnatal mammary gland development (9,10). More recently, it had been shown that Cre-mediated invalidation of this gene affects final differentiation of the gland during gestation (11).…”
mentioning
confidence: 99%